The Behavior of the Laboratory Rat 2004
DOI: 10.1093/acprof:oso/9780195162851.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensation

Abstract: This chapter discusses five principles for how sensorimotor behaviors are learned and performed by rats, based on new findings from neuroscience. It focuses on nonvibrissal somatosensory processing but also considers examples from the whisker-tactile system or from other sensory modalities. These principles are: (i) analyzed somatosensory feedback information is constantly influencing the ascending somatosensory data stream in rats; (ii) rats are constantly evaluating information across multiple timescales to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The present results also support arguments that exposure to the spatial terms of their language can guide infants in forming particular spatial categories (Bowerman & Choi, 2001;Choi & Bowerman, 1991), although the present results pinpoint this effect more specifically to infants' ability to form these categories under more challenging conditions. At a broader level, the present results also align with arguments that acquiring spatial language serves to advance and at times restructure early concepts (Hermer-Vazquez, Moffet, & Munkholm, 2001;Xu, 2016). We expand on these views by raising the possibility that which spatial terms children acquire may shape how easily they generalize across diverse exemplars of a spatial relation to form an abstract spatial category.…”
Section: Discussionsupporting
confidence: 85%
“…The present results also support arguments that exposure to the spatial terms of their language can guide infants in forming particular spatial categories (Bowerman & Choi, 2001;Choi & Bowerman, 1991), although the present results pinpoint this effect more specifically to infants' ability to form these categories under more challenging conditions. At a broader level, the present results also align with arguments that acquiring spatial language serves to advance and at times restructure early concepts (Hermer-Vazquez, Moffet, & Munkholm, 2001;Xu, 2016). We expand on these views by raising the possibility that which spatial terms children acquire may shape how easily they generalize across diverse exemplars of a spatial relation to form an abstract spatial category.…”
Section: Discussionsupporting
confidence: 85%
“…Between 5 and 8 years of age, children's behaviour in reorientation tasks undergoes a qualitative change: instead of navigating separately by the shape of the environment and the position of a distinctive landmark, children begin to combine representations of surface layouts and landmark objects productively, so as to locate directly an object hidden at a particular distance and direction from a landmark [66,67]. This change occurs when children begin systematically to produce spatial expressions, including the terms left and right [66,68]. A recent study of adult speakers of an emerging language suggests that the acquisition of spatial language plays a causal role in the emergence of this new navigational pattern [69].…”
Section: Core Knowledge and Geometrical Intuitionmentioning
confidence: 99%
“…On one hand, as noted above, comparative cognition research has suggested that conjoining of geometric and nongeometric information can be achieved in several species, irrespective of possession of a verbal language (one very interesting suggestion put forward by Spelke, 1994, 1996, is in fact that language can serve as the medium to integrate information from different modules; see also Hermer-Vasquez, Spelke, & Katsnelson, 1999;Hermer-Vasquez, Moffet, & Munkholm, 2001). On the other hand, a weaker version of modularity can be claimed for based on the observation of a ''primacy'' of geometric information over nongeometric information.…”
Section: Introductionmentioning
confidence: 97%